Zika virus: oral healthcare implications. (12th July 2016) - Leão, JC; Gueiros, LA; Lodi, G; Robinson, NA; Scully, C
Abstract : Zika virus (ZIKV) infection has been recognised since 1947, but just recently it became a worldwide major public health problem. The most common features of ZIKV infection are fever, cutaneous rash, arthralgia and conjunctivitis but most affected patients with the clinical disease present with only mild symptoms. However, severe neurological complications have been described: there is an occasional association with Guillain–Barre syndrome, and emerging data indicate an association between vertical transmission of ZIKV infection and microcephaly, but no specific orofacial manifestations have yet been reported. ZIKV is present in body fluids and has also been demonstrated in the saliva, but there is as yet no reliable evidence to support ZIKV transmission via this pathway. Transmission in oral health care should be effectively prevented using standard infection control measures. There are currently no specific treatments for Zika virus disease and no vaccines available, so prevention of ZIKV is based on vector control.